High level of intraoperative lactate might predict acute kidney injury in aortic arch surgery via minimally invasive approach in patients with type A dissection - Lyu, Ying; Liu, Yu; Xiao, Xiong; Yang, Zhonglu; Ge, Yuguang; Jiang, Hui (Frontiers in Cardiovascular Medicine, 2023)
Background A high incidence of acute kidney injury (AKI) has been recorded in total arch replacement (TAR) combined with frozen elephant trunk (FET) implantation in patients with acute type A dissection (ATAAD) via median sternotomy approach with some risk factors. However, the independent risk factors for AKI via a minimally invasive approach have not yet been identified. Methods A total of 207 patients with ATAAD were enrolled from January 2018 and November 2019 and were divided into AKI and non-AKI groups. The current surgical strategy was TAR combined with FET via a single upper hemisternotomy approach, a minimally invasive method. An increase in the serum creatinine (Cr) level to ≥2 times the baseline level 48 h post-surgery was defined as AKI. The morbidity of AKI was investigated with a step-by-step backward multivariate analysis of its independent risk factors and a receiver-operating characteristic curve analysis. Results Postoperative AKI was observed in 39 (18.8%) patients, and the total hospital mortality was 8.7%. Univariate analysis found that preoperative Cr, weight, circulatory arrest time ≥60 min, intraoperative highest lactate (Lac), and intraoperative transfusion had significant differences between the two groups. However, multivariate step-by-step backward logistic regression analysis identified intraoperative highest Lac and transfusion as independent risk factors for postoperative AKI and intraoperative highest Lac was identified as the most critical independent risk factor estimated by the partial chi-square statistic minus the predicted degrees of freedom with 4.3 mmol/L as the optimal cut-off point for prediction for AKI. Conclusions Intraoperative highest Lac and transfusion were independent risk factors for postoperative AKI, which led to high hospital mortality. Moreover, intraoperative highest Lac was the most critical independent risk factor and high level of intraoperative highest Lac (4.3 mmol/L) might predict for postoperative AKI.